From Maternal Grazing to Barn Feeding During Pre-weaning Period: Altered Gastrointestinal Microbiota Contributes to Change the Development and Function of the Rumen and Intestine of Yak Calves - Cui, Zhanhong; Wu, Shengru; Liu, Shujie; Sun, Lu; Feng, Yuzhe; Cao, Yangchun; Chai, Shatuo; Zhang, Guomo; Yao, Junhu (Frontiers in Microbiology, 2020)
Understanding the altered gastrointestinal microbiota is important to illuminate effects of maternal grazing (MG: maternally nursed and grazed) and barn feeding (BF: supplied milk replacer, starter feed, and alfalfa hay) on the performance and immune function of yak calves. Compared with the MG group, the significantly increased body weight, body height, body length, chest girth, and organ development of liver, spleen, and thymus were identified in the BF group, which were resulted from the significantly increased dry matter intake, increased concentrations of propionate, butyrate, isobutyrate, and valerate, increased ruminal pectinase, duodenal α-amylase, jejunal α-amylase and trypsin, and ileal trypsin, and promoted gastrointestinal epithelial development. Furthermore, genera of Sharpea, Sphingomonas, Atopobium, Syntrophococcus, Clostridium_XIVb, Acinetobacter, Oscillibacter, Dialister, Desulfovibrio, Bacteroides, Lachnospiracea_incertae_sedis, and Clostridium_sensu_stricto, which were involved in utilization of non-fibrous carbohydrate and further beneficial to improve the gastrointestinal digestion, development, and immune functions, were significantly increased in the BF group. Meanwhile, the significantly enhanced ruminal epithelial immune functions and intestinal immune functions based on enhanced ruminal immune related pathway, duodenal IL-1β, jejunal IL-1β, IL-2, TNF-α, and IFN-γ, and ileal IL-1β were identified in the BF group, which also may induced by the increased abundance of gastrointestinal microbiota. Overall, barn feeding significantly increased the diversity of species and abundance of microbes which used different carbohydrates and further benefit to the growth and immune function of yak calves.